Glass composition, glass substrate and application
By optimizing the alkali-free glass formula and using composite clarifiers, the problems of high energy consumption and short kiln system life during alkali-free glass firing are solved, and glass compositions and glass substrates with low energy consumption and low melting temperature are achieved, which improves manufacturing efficiency and product performance.
Patent Information
- Application Number
- CN202411010625.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-07-26
AI Technical Summary
The existing alkali-free glass has high energy consumption during firing, and the kiln system is prone to corrosion, resulting in a short system life. There are problems such as high cost and difficult to break through in the manufacturing of TFT-LCD glass substrates.
Using a glass composition formula, including SiO2, Al2O3, H3BO3, RO, Gd2O3, clarifier and Bi2O3, by optimizing the content ratio of Al2O3 and RO, and using a mixture of composite clarifiers SnO2, Na2SO4, and NaCl, the melting and clarification temperature of the glass liquid are reduced, the clarification time is shortened, and the thinness and performance of the glass substrate are improved.
The low melting temperature, low clarification temperature and low molding temperature of the glass composition are achieved, which shortens the production time of the glass substrate, reduces energy consumption, extends the life of the kiln system, and improves the mechanical properties and thermal stability of the glass substrate.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass, and in particular relates to a glass composition, a glass substrate and applications. Background Art
[0002] Alkali-free glass is a high-silicon oxide glass. By removing alkali metals during the manufacturing process, it has high alkali resistance and stability. Alkali-free glass is widely used in TFT-LCD (thin-film transistor liquid crystal display); the relevant technology of alkali-free glass is mainly mastered by international glass production giants such as Corning, Asahi Glass, and Electric Glass; although China is the world's largest producer of flat glass, it currently relies mainly on imports for thin electronic glass for TFT-LCD, and domestic companies such as Rainbow Group, Dongxu, and Koli Vision are still in the initial stage of this technology; there is a large gap in TFT-LCD glass substrates in my country, and domestic practitioners are currently facing problems such as high cost and difficulty in breaking through large sizes. The high cost is mainly reflected in the high energy consumption during the firing process of alkali-free glass, the corrosion of alkali-free glass to the kiln system, and the short life of the kiln system caused by high temperature damage.
[0003] In the prior art, the invention patent with publication number CN105452182B discloses an alkali-free glass, which contains SiO2 66% to 78%, Al2O3 8% to 15%, B2O3 0.99% to 1.8%, MgO 0% to 8%, CaO 5.42% to 15%, SrO 0% to 8%, and BaO 1% to 8% as glass composition, with a molar ratio of SrO / (MgO+CaO+SrO+BaO) of less than 0.09, does not contain Y2O3 and La2O3, does not contain alkali metal oxides substantially, and has a strain point higher than 725°C; the invention patent with publication number JP6202353B2 discloses an alkali-free glass, which contains SiO2 60 to 69%, Al2O3 9.5 to 17%, B2O3 0 to 7.3%, MgO 0 to 8%, CaO 2~15%, SrO 0.1~1.3%, BaO 0.5~3.1%, ZnO 0~5%; Al2O3 is used in these alkali-free glass formulas to reduce the crystallization tendency of glass and improve the mechanical properties of glass, but a high content of Al2O3 will increase the viscosity of the glass liquid, making melting and clarification difficult, and increasing the crystallization tendency; the invention patent with publication number KR102354231B1 discloses a glass composition, which, based on the total weight of oxides, contains 45-47% by weight of SiO2, 21.5-25% by weight of Al2O3, 5-2% by weight of MgO, 13-16% by weight of Na2O, 11-15% by weight of P2O5 and 1-1.8% by weight of TiO2; the glass formula is not an alkali-free glass formula and has a high Na2O content.
[0004] Developing a low-energy, alkali-free glass formula with independent intellectual property rights can not only break the monopoly of foreign companies on intellectual property rights, but also contribute to the development of my country's TFT-LCD glass substrate industry. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a glass composition, a glass substrate and applications, which have low melting temperature, clarification temperature and forming temperature, short clarification time, thin glass substrate, low liquidus temperature and low expansion coefficient.
[0006] The content of the present invention includes:
[0007] A glass composition comprising the following components in parts by weight:
[0008] SiO2 65-70%, Al2O3 2-5%, H3BO3 0.1-2.5%, RO 18-20%, Gd2O3 2-5%, clarifier 2-5%, Bi2O3 1-2%;
[0009] The RO is one or more of CaO, MgO and ZnO;
[0010] The mass ratio of (Al2O3+RO) / H3BO3 is in the range of 1:0.05-0.12;
[0011] The Al2O3 is composed of α-Al2O3 and γ-Al2O3, wherein the content of α-Al2O3 accounts for 30-40%.
[0012] In one embodiment, the clarifier is a mixture of SnO2, Na2SO4, and NaCl, and the mass ratio of SnO2, Na2SO4, and NaCl is 2:0.05-0.15:0.05-0.15, and preferably the mass ratio of SnO2, Na2SO4, and NaCl is 2:0.10:0.10.
[0013] In one embodiment, the mass ratio of (Al2O3+RO) / H3BO3 is 1:0.10.
[0014] In one of the embodiments, the content of α-Al2O3 is 40%.
[0015] In one embodiment, when the RO is a mixture of CaO and MgO, the weight content of CaO accounts for 80%.
[0016] Another aspect of the present invention provides a glass substrate made from any one of the glass compositions described above, wherein the thickness of the glass substrate is 0.3-0.6 mm.
[0017] In one embodiment, the liquidus temperature of the glass substrate is below 1150°C.
[0018] In one embodiment, the expansion coefficient of the glass substrate is 2.6×10 -6 / ℃~3.2×10 -6 / ℃.
[0019] Another aspect of the present invention provides a use of any of the glass compositions described above or any of the glass substrates described above in preparing a display.
[0020] Al2O3 can reduce the crystallization tendency of glass, improve chemical stability and mechanical strength, and improve thermal stability. However, when the Al2O3 content is greater than 5%, it will increase the viscosity of the glass liquid, making melting and clarification difficult, increase the crystallization tendency, and cause defects such as ripples on the glass substrate.
[0021] In the crystal structure of α-Al2O3, the face composed of three oxygen atoms is shared by two adjacent octahedra. The entire crystal can be seen as a large "molecule" composed of countless octahedra [AlO6] bonded together through the same face. This structure makes α-alumina very stable. α-Al2O3 is the most stable of all Al2O3 crystal forms and is often used in glass formulations to reduce the melting and clarification temperatures of glass. However, when its content is high, the expansion coefficient of the molten glass will be higher and the softening temperature will be lower.
[0022] The crystal structure of γ-Al2O3 is O 2- The cubic close packing produces an octahedral structure, and the octahedrons form interconnected tetrahedrons to form a spinel structure; γ-Al2O3 has adsorption capacity and chemical activity due to its cubic crystal structure, and is often used as an adsorbent.
[0023] CaO can reduce the high-temperature viscosity of the glass liquid and promote the melting and clarification of the glass liquid; when the temperature decreases, it can increase the viscosity of the glass liquid; but as the content increases, it will increase the crystallization tendency of the glass, reduce the thermal stability of the glass, and increase the annealing temperature.
[0024] MgO has a similar effect to CaO, but does not have the crystallization tendency of calcium oxide. Therefore, MgO can be used to replace CaO in appropriate amounts.
[0025] ZnO is used as a glass flux to increase transparency, brightness and resistance to tensile deformation, and to reduce the coefficient of thermal expansion. It has found new uses in optical glass, electrical glass and low-melting-point glass.
[0026] Gd2O3 can effectively improve the weather resistance of glass and increase the refractive index of glass, but when its content is higher than 8%, the chemical stability of the glass will deteriorate, therefore, its content is below 8%.
[0027] Bi2O3 has high compressive strength and good wear resistance and is widely used in glass manufacturing; bismuth oxide can also improve the chemical resistance and optical properties of glass, making the glass have better transparency and refractive index.
[0028] H3BO3 can improve the heat resistance and transparency of glass products, increase mechanical strength and shorten melting time. H3BO3 is a white flaky triclinic crystal with a special luster. It is easily soluble in water. When heated to 100°C, it loses water and partially decomposes into metaboric acid (HBO2).
[0029]
[0030] At 140~160℃, it turns into tetraboric acid (H2B4O7), and if heated further it will completely turn into molten B2O3.
[0031]
[0032] B2O3 is a glass-forming oxide. When melted at high temperatures, B2O3 is converted into boron-oxygen triangles [BO3] and tetrahedrons [BO4], which together with silicon-oxygen tetrahedrons form a structural network to form borosilicate glass.
[0033] Among glass clarifiers, composite clarifiers have a much stronger effect than single clarifiers, with faster clarification speed and significantly shorter clarification time. Tin oxide (SnO2) is a redox chemical clarifier. When the temperature is higher than 1500°C, it will decompose into stannous oxide and release clarification gas O2. The bubbles will expand to a large enough size and rise to the surface of the glass, and the gas will be discharged from the glass melt. When the temperature drops, SnO (stannous oxide) can absorb O2 in the residual bubbles in the glass melt and form SnO2 (tin oxide) again. The gas is stabilized through the redox balance of SnO2 / SnO, and the bubble defects in the glass melt are gradually reduced. Sodium chloride (NaCl) is a high-temperature volatile clarifier. It can reduce the viscosity and surface tension of the glass at high temperatures, and the Cl2 decomposed at high temperatures plays a clarifying role. The solubility of Cl2 increases with the increase of alkalinity in the glass liquid. The greater the saturation of dissolved gas in the glass liquid, the lower the partial pressure of gas in the bubbles in the glass liquid, the faster the bubble growth rate, the larger the bubble is and the higher it rises, the faster the bubble disappears, and the number of bubbles decreases, which accelerates clarification. Na2SO4 decomposes into Na2O and SO3 at high temperature. SO3 gas forms bubbles and fuses other gases in the glass liquid. After the bubbles grow further, they float to the surface of the glass liquid and are released into the environment, further reducing the bubble content of the glass. Na2SO4 is often used as a clarifier in float glass.
[0034] Beneficial effects of the present invention:
[0035] (1) In the glass composition formula of the present invention, appropriate amounts of Al2O3 and alkaline earth metal oxide RO can promote the melting and clarification of the glass liquid, but too much content will increase the crystallization tendency of the glass liquid. H3BO3 can shorten the melting time of the glass, and too little or too much content will affect the melting and reaction time of the glass. When the mass ratio of (Al2O3+RO) / H3BO3 is in the range of 1:0.05-0.12, the viscosity of the glass composition is the smallest, and its melting temperature, clarification temperature, and forming temperature are significantly reduced, which is 20-80°C lower than the corresponding temperature of the existing glass formula, thereby greatly extending the life of the production line equipment;
[0036] (2) In the glass composition formula of the present application, the glass composition obtained by the appropriate ratio of α-Al2O3 and γ-Al2O3 has a low melting temperature and a low clearing temperature, while the glass expansion coefficient does not increase, and the softening temperature does not decrease significantly, and the glass has good properties;
[0037] (3) In the glass composition formula of the present invention, a mixture of composite clarifiers SnO2, Na2SO4, and NaCl is used, and the advantages of the three clarifiers of oxygen clarifier, sulfur clarifier, and halogen clarifier are utilized to give full play to the synergistic effect and superposition effect of the three clarifiers, so as to achieve a continuous clarification effect and greatly enhance the clarification ability;
[0038] (4) The glass substrate of the present invention has a thickness of 0.3-0.6 mm, which is a relatively thin glass substrate; the liquidus temperature of the glass substrate is low, which is below 1150°C; and the expansion coefficient of the glass substrate is small, which is 2.6×10 -6 / ℃~3.2×10 -6 / ℃. DETAILED DESCRIPTION
[0039] Example 1
[0040] A glass composition comprising the following components in parts by weight:
[0041] SiO266%, Al2O32%, H3BO32%, CaO 14.4%, MgO 3.6%, Gd2O35%, clarifier 5%, Bi2O32%; among them, α-Al2O3 accounts for 40% and γ-Al2O3 accounts for 60% in Al2O3; the clarifier composition is SnO2, Na2SO4, NaCl with a mass ratio of 2:0.10:0.10;
[0042] Steps for preparing glass substrate:
[0043] (1) Melting: Place the glass composition in the above-mentioned weight parts into a kiln system, stir evenly, and heat to 1500-1600° C. until the glass composition is completely melted. Measure the melting temperature of the completely melted state of the glass composition.
[0044] (2) Clarification: The molten glass enters the clarification channel, where it is heated to above 1620°C and efficiently stirred and homogenized to perform the clarification operation of the glass;
[0045] (3) Overflow forming: After the glass liquid is clarified, the molten glass liquid with appropriate viscosity is allowed to overflow from the overflow trough along the overflow brick walls on both sides, merge into one to form a glass flat plate, and then pull it down to control the thickness of the pulled-down glass plate. Annealing is performed to eliminate the residual stress of the glass plate to obtain a glass substrate.
[0046] Example 2
[0047] A glass composition comprising the following components in parts by weight:
[0048] SiO2 70%, Al2O3 2%, H3BO 32%, CaO 20%, Gd2O32%, clarifier 3%, Bi2O3 1%; wherein, α-Al2O3 accounts for 30%, γ-Al2O3 accounts for 70%; the clarifier consists of SnO2, Na2SO4, NaCl, with a mass ratio of 2:0.08:0.08; the steps for preparing the glass substrate are the same as those in Example 1.
[0049] Example 3
[0050] A glass composition comprising the following components in parts by weight:
[0051] SiO2 66%, Al2O3 3%, H3BO3 1.5%, CaO 12%, MgO 4%, ZnO 2%, Gd2O3 4.5%, clarifier 5%, Bi2O3 2%; wherein, α-Al2O3 accounts for 40%, γ-Al2O3 accounts for 60%; the clarifier consists of SnO2, Na2SO4, NaCl, and the mass ratio is 2:0.10:0.10; the steps for preparing the glass substrate are the same as those in Example 1.
[0052] Example 4
[0053] A glass composition comprising the following components in parts by weight:
[0054] SiO2 66%, Al2O3 2%, H3BO 32%, CaO 14.4%, MgO 3.6%, Gd2O3 5%, clarifier 5%, Bi2O3 2%; among them, α-Al2O3 accounts for 35%, γ-Al2O3 accounts for 65%; the clarifier consists of SnO2, Na2SO4, and NaCl, with a mass ratio of 2:0.10:0.10.
[0055] Comparative Example 1
[0056] A glass composition comprising the following components in parts by weight:
[0057] SiO2 66%, Al2O3 3.5%, H3BO3 0.5%, CaO 14.4%, MgO 3.6%, Gd2O3 5%, clarifier 5%, Bi2O3 2%; wherein, α-Al2O3 accounts for 40%, γ-Al2O3 accounts for 60%; the clarifier consists of SnO2, Na2SO4, NaCl, and the mass ratio is 2:0.10:0.10; the steps for preparing the glass substrate are the same as those in Example 1.
[0058] Comparative Example 2
[0059] A glass composition comprising the following components in parts by weight:
[0060] SiO2 66%, Al2O3 2%, H3BO3 2.5%, CaO 14.4%, MgO 3.6%, Gd2O3 5%, clarifier 4.5%, Bi2O3 2%; wherein, α-Al2O3 accounts for 40%, γ-Al2O3 accounts for 60%; the clarifier consists of SnO2, Na2SO4, NaCl, and the mass ratio is 2:0.10:0.10; the steps for preparing the glass substrate are the same as those in Example 1.
[0061] Comparative Example 3
[0062] The proportion of α-Al2O3 in Example 1 is 30%, and the proportion of γ-Al2O3 is 70%. These are replaced by α-Al2O3 accounting for 70% and γ-Al2O3 accounting for 30%, and the rest are the same as in Example 1.
[0063] Comparative Example 4
[0064] The mass ratio of SnO2, Na2SO4 and NaCl in the clarifier of Example 1 is 2:1:1, and the rest is the same as Example 1.
[0065] The relevant test results are as follows:
[0066]
[0067] The (Al2O3+RO) / H3BO3 of Examples 1-4 is within the range of 1:0.05-0.12, and the content of α-Al2O3 is within the range of 30-40%. The obtained glass substrates have good properties, especially Example 1 has the lowest melting temperature and liquidus temperature; the values of (Al2O3+RO) / H3BO3 of Comparative Examples 1 and 2 are not within the scope of the present application, and their melting temperatures and liquidus temperatures are significantly increased; Comparative Example 3 swaps the content ratios of α-Al2O3 and γ-Al2O3, resulting in an increase in the thermal expansion coefficient, the melting temperature of the glass, and the liquidus temperature; the ratios of SnO2, Na2SO4, and NaCl in the composite clarifier of Comparative Example 4 are not within the scope of the present application, the glass clarification speed is reduced, and the clarification time is prolonged.
[0068] A person skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of protection of the present application is limited to these examples. In line with the concept of the present application, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of different aspects of one or more embodiments of the present application as described above, which are not provided in detail for the sake of simplicity.
[0069] One or more embodiments of the present application are intended to cover all such substitutions, modifications and variations that fall within the broad scope of the present application. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of one or more embodiments of the present application should be included in the protection scope of the present application.
Claims
1. A glass composition, characterized in that: The invention comprises the following components in percentage by weight: SiO2 65-70%, Al2O3 2-5%, H3BO3 0.1-2.5%, RO 18-20%, Gd2O3 2-5%, clarifier 2-5%, Bi2O3 1-2%; The RO is one or more of CaO, MgO and ZnO; The mass ratio of (Al2O3+RO) / H3BO3 ranges from 1:0.05 to 0.12; The Al2O3 is composed of α-Al2O3 and γ-Al2O3, wherein the content of α-Al2O3 accounts for 30-40%; The clarifier is a mixture of SnO2, Na2SO4, and NaCl, and the mass ratio of SnO2, Na2SO4, and NaCl is 2:(0.05-0.15):(0.05-0.15).
2. The glass composition according to claim 1, characterized in that: The mass ratio of SnO2, Na2SO4 and NaCl is 2:0.10:0.
10.
3. The glass composition according to claim 1, wherein: The mass ratio of (Al2O3+RO) / H3BO3 is 1:0.
10.
4. The glass composition according to claim 1, wherein: The content of α-Al2O3 accounts for 40%.
5. The glass composition according to any one of claims 1 to 4, characterized in that: When the RO is a mixture of CaO and MgO, the weight content of CaO accounts for 80%.
6. A glass substrate made from the glass composition according to any one of claims 1 to 5, characterized in that: The glass substrate has a thickness of 0.3-0.6 mm.
7. The glass substrate according to claim 6, wherein: The liquidus temperature of the glass substrate is below 1150°C.
8. The glass substrate according to claim 6 or 7, wherein: The expansion coefficient of the glass substrate is 2.6×10 -6 / ℃~3.2×10 -6 / ℃.
9. Use of the glass composition according to any one of claims 1 to 5 or the glass substrate according to any one of claims 6 to 8 in preparing a display.
Citation Information
Patent Citations
Alkali-free glass
CN105452182B
Alkali-free glass
JP6202353B2
Compositions for glass and glass and their manufacturing methods and applications
KR102354231B1
High-strain point alkali-free aluminoborosilicate glass and preparation method thereof
CN108503214A
Alkali-free glass
CN110885187A